2016
DOI: 10.1002/2016jd025388
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol effects on summer monsoon over Asia during 1980s and 1990s

Abstract: The Community Earth System Model is used to study the aerosol climate effects during the 1980s and 1990s in which the anthropogenic SO2 emissions decreased in North America and Western Europe and increased in East and South Asia. From the 100 year simulations, aerosol forcing results in cooler (−0.13 K) and drier (−0.01 mm/day) atmosphere with less shortwave radiation flux at the surface (−0.37 W/m2). The clear‐sky shortwave radiation flux decreased over East Asia (−0.81 W/m2) and South Asia (−1.09 W/m2), but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Atmospheric aerosols and monsoon circulation over East Asia are strongly coupled. The distribution of aerosol is determined by the atmospheric circulation, and deposition processes, while the circulation is affected by the aerosol (Liu et al 2011;Tao et al 1 3 2012; Liao et al 2015;Wu et al 2015;Li et al 2016;Tsai et al 2016). Aerosol emission changes have the potential to affect both regional and global climate by altering the radiation budget directly and interacting with clouds through microphysical processes, thereby causing subsequent changes in surface temperature, and the local and global hydrological cycle (e.g., Giorgi et al 2003;Rosenfeld et al 2008;Stevens and Feingold 2009;Liu et al 2011;Tao et al 2012;Levy et al 2013;Stjern and Kristjansson 2015;Wang et al 2015;Kim et al 2016;Xie et al 2016a, b;Lau and Kim 2017;Li et al 2016Li et al , 2018Wilcox et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Atmospheric aerosols and monsoon circulation over East Asia are strongly coupled. The distribution of aerosol is determined by the atmospheric circulation, and deposition processes, while the circulation is affected by the aerosol (Liu et al 2011;Tao et al 1 3 2012; Liao et al 2015;Wu et al 2015;Li et al 2016;Tsai et al 2016). Aerosol emission changes have the potential to affect both regional and global climate by altering the radiation budget directly and interacting with clouds through microphysical processes, thereby causing subsequent changes in surface temperature, and the local and global hydrological cycle (e.g., Giorgi et al 2003;Rosenfeld et al 2008;Stevens and Feingold 2009;Liu et al 2011;Tao et al 2012;Levy et al 2013;Stjern and Kristjansson 2015;Wang et al 2015;Kim et al 2016;Xie et al 2016a, b;Lau and Kim 2017;Li et al 2016Li et al , 2018Wilcox et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is known as the aerosol indirect effects or aerosol-cloud interaction (ACI) (Boucher et al 2013). The radiative and cloud processes can interact with each other and produce complex aerosol effects on clouds, precipitation, and extreme precipitation, both locally and remotely to emission regions (e.g., Chou et al 2005;Bollasina et al 2014;Dong et al 2016;Tsai et al 2016;Xie et al 2016a, b;Wang et al 2017a;Zhang et al 2017;Lin et al 2018;Wilcox et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling studies suggest a role for both local and nonlocal aerosols in weakening monsoons in Asia (Cowan & Cai, ; Dong et al, ; Guo et al, ) and West Africa (Dong, Sutton, et al, ), though local aerosol emissions are suggested to be predominantly responsible for the drying of the South Asian monsoon (Bollasina et al, ; Ganguly et al, ; Guo et al, ; Salzmann et al, ). Some other studies looked at the effect of the simultaneous increase of Asian emissions and decrease of North American and European emissions (Tsai et al, ), but the relative influence of aerosols from different regions on the various monsoon systems still remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%